THE REALIZATION OF COHESION IN READING TEXTS USED IN CHICKEN SOUP FOR THE SOUL IN THE CLASSROOM (English Education Journal, 2012)
Studi ini bertujuan untuk mencari penerapan dari grammar dan lexical cohesive pada buku “Chicken Soup for The Soul in classroom”. 10 teks dipilih dalam penelitian ini dan dianalisa melalui pendekatan deskriptif. Teori kohesi dari Halliday dan Hasan 91976) digunakan untuk menganalisa teks. Studi menunjukan bahwa referensi mempunyai frekuensi tertinggi pada occurrence, diikuti lexical, konjungsi, ellipsis, dan substitusi. Personal reference dan temporal konjungsi sering ditemukan pada teks yang mengindikasikan bahwa teks bergebre recount. Berdasarkan analisis qualitative, dutemukan bahwa teks bersifat kohesif karena level dari kohesif yang mencapai  95%. Dari temuan, dapat disimpulkan bahwateks memenuhi criteria baik dan dapat digunakan sebagai alternative untuk pengajaran recount teks bagi siswa.This study aims at finding out the realization of grammatical and lexical cohesive devices in reading texts from the book entitled “Chicken Soup for the Soul in the Classroom”. The ten reading texts were selected as the corpus of the study. They were then analyzed using qualitative descriptive approach. The theory of cohesion proposed by Halliday and Hasan (1976) was used as framework for analyzing the texts. The result of the study shows that reference had the highest frequency of occurrences. Then it was followed by lexical, conjunction, ellipsis, and substitution. Personal reference and temporal conjunction most frequently occurred in the texts. Therefore, it can be concluded that the texts belong to recount texts. Based on the qualitative analysis, it was found out that the texts are considered to be cohesive because the level of cohesiveness are very high, i.e. more than 95%. From the result of the study, it can be concluded that the texts fulfill the requirements of becoming a good text and they can be used as alternative material for teaching recount texts for Indonesian students.